Examining the dark side of motivation on life satisfaction in college students: does grit matter? - Huéscar Hernández, Elisa (2021)
Even though teachers can have an important effect on the regulation of student behavior, the existing scientific literature has hardly explored the simultaneous influence of personal traits and social factors to promote student well-being. This study examined the mediating role of amotivated behavior and the relationship with teacher controlling behaviors, grit, and satisfaction with life. A total of 474 college students (female= 135; male= 339) participated in the study. All participants completed a multi-section survey assessing the constructs under analysis. Results from the structural model analysis displayed acceptable fit and amotivation played a mediating role in the relationship between grit-perseverance and life satisfaction but not for grit-passion. These findings provide evidence regarding adequate teacher behavior and the importance of measuring student grit in the classroom setting. These findings provide new insights into the understanding of teacher motivational behaviors and student learning processes that influence student behavioral regulations and affective outcomes.